Vitamin D and COVID-19: Inmunomodulatory Effects and the Mexican Public Health Perspectives - María Muñoz-Almaguer; Erick Flores-Salas; Carlos Bancalari-Organista; Raymundo Escutia-Gutierrez; María Virgen-Montelongo; Felipe Avalos-Salgado; Esmeralda Franco-Torres; Ana Corona-España (International Journal of Molecular Sciences, 2026)
Vitamin D is a fat-soluble vitamin, considered a prohormone, that plays a fundamental role in calcium absorption and reabsorption, as well as the modulation of inflammatory response in infectious conditions such as COVID-19. A literature search was conducted in scientific databases and official sources, selecting studies published in the last 10 years in Spanish and English related to vitamin D and COVID-19; studies unrelated to the nutritional approach were excluded to reduce bias and ensure a rigorous and reproducible analysis. It was observed that the probability of contracting COVID-19 increases as the D3 hypovitaminosis prevalence increases. In Mexico, the relevance of vitamin D deficiency or supplementation in this disease has been controversial. Some studies claim that vitamin D supplementation could be a protective factor. According to the National Health Survey in Mexico (Ensanut), the Mexican population has significant deficiencies in this vitamin, contributing to an unfavorable diagnosis, particularly for children and pregnant women, as it is considered a deficiency in the blood when it is below 30 ng/mL and insufficiency when below 20 ng/mL, making these deficiencies important risk factors in the development of COVID-19 severe cases. Nevertheless, the use of vitamin D as an adjuvant agent in the treatment of COVID-19 can represent one of the main options for public health, providing therapeutic properties and health benefits.